2022
DOI: 10.2147/jmdh.s371361
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices Regarding Ergonomic Hazards Among Healthcare Workers in a Saudi Government Hospital

Abstract: Background: Musculoskeletal disorders (MSDs) affecting healthcare workers (HCWs) must be considered and addressed as a serious issue. Thus, it is important to incorporate ergonomics into clinical practice to prevent MSDs. The objectives of this study were to investigate HCWs' knowledge, attitudes, and practices regarding ergonomics in a large governmental healthcare facility. Methods: A cross-sectional study was conducted in which the participants were interviewed to complete a validated four-section questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In the current study, 89% of the participants had positive attitude towards maintenance of good posture during activities of daily living. This finding is consistent with the result of a study by Al hazim et al, [17] where they reported that, greater proportion of undergraduate in Faculty of Dentistry, Tanta University, Egypt had positive attitude towards ergonomics. This is also similar to findings of Al hazim et al, [7] where 83.2 % of the participants showed positive attitude towards good posture.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, 89% of the participants had positive attitude towards maintenance of good posture during activities of daily living. This finding is consistent with the result of a study by Al hazim et al, [17] where they reported that, greater proportion of undergraduate in Faculty of Dentistry, Tanta University, Egypt had positive attitude towards ergonomics. This is also similar to findings of Al hazim et al, [7] where 83.2 % of the participants showed positive attitude towards good posture.…”
Section: Discussionsupporting
confidence: 92%
“…The observations revealed that the participants' working postures improved significantly after the ergonomic education sessions. Similar results were obtained from a study conducted among healthcare professionals in the eastern province of Saudi Arabia [ 14 ]. The consequences of inappropriate work posture are often chronic, cumulative, and severe.…”
Section: Discussionsupporting
confidence: 88%
“…This increased the likelihood of symptoms in the lower limbs owing to the need to maintain the lower limbs in inappropriate postures and the high biomechanical load resulting from moving patients. However, Alhazim et al [ 48 ] highlighted that redesigning workstations is not enough to prevent MSDs, and efforts should also focus on labor practices, especially those related to ergonomics. Thus, inadequate workstations and absence of ergonomic practices are ideal conditions for worsening symptoms in the lower limbs.…”
Section: Discussionmentioning
confidence: 99%